Factor to Predict Difficultyin Laparoscopic Cholecystectomy - Samintharapanya, Sahatham (Lampang Medical Journal, 2022)
Background : Currently laparoscopic cholecystectomy (LC) is the standard treatment for gallbladder diseases instead of open surgery. The operative difficulty and complication are still variable. Objective : To determine the predicting factors of LC difficulty. Material and Method : Medical records of 139 patients who underwent LC by single surgeon in Lampang Hospital between September 2002 - June 2009 was retrospectively reviewed. Inclusion criteria included symptomatic gallstone, acute cholecystitis within 72 hours after onset, resolved cholecystitis beyond 4 weeks and gallstone pancreatitis. It was categorized into 4 groups of operative time: easy (< 60 minutes), intermediate (60-120 minutes), difficult (>120 minutes) and conversion to open surgery group. Demographic data, number of abdominal ports, length of stay (LOS) and complications were recorded. The data were analyzed by Pearson’s chi-square test and Kruskal–Wallis test. Results : Most of the patients were female (74.1%). The mean age was 53 years (range, 22-80); 21.6% was in easy group, 53.9% intermediate, 20.2% difficult and 4.3% in conversion group. Age, sex, body weight, ASA class, co-morbidity and previous abdominal surgery did not affect the operative time. Preoperative diagnosis was the only factor correlating with LC difficulty. Acute cholecystitis increased the operative time (p<0.001) whereas symptomatic gallstone and resolved cholecystitis consumed less operative time (p =0.003 and 0.038 respectively). The easy group used less number of abdominal ports than the difficult and conversion groups, as well as shorter LOS and less complication (p=0.002 and <0.001 respectively). Conclusion : Preoperative diagnosis was the only factor to predict difficulty in laparoscopic cholecystectomy. Acute cholecystitis increased more difficulty and complication than postponed surgery until the inflammation resolved.